THE RESULTS OF DETERMINING THE ACTUAL VALUES OF TRACK STIFFNESS TO STUDY THE INTERACTION OF TRACK AND ROLLING STOCK - Taturevych, A. P. (Science and Transport Progress, 2003)
The results of determining the rigidity and the modulus of elasticity of the track are shown in the paper. They are used for research of track and a rolling stock interaction and they are faking info account the constructions of the permanent way which has been changed for last years especially on concrete crossties. The values of the elasticity modules under the rail are specified under the horizontal bend and rail twist.